(NmATEMATI^ESKIE TERMINY (B:s (NsPRAWO^NO(B-(NBIBLIOGRAFI^ESKIJ SLOWARX (B/s - (NkARTAWOW(B, (NsERGEJ aLEKSEEWI^s; (NkOWALENKO(B, (Nw(B.(Ns(B.s ((NkIEW (B:s (NwY]A [KOLA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 294-295s
Keywords: (NmATEMATIKA (B- (NsLOWARIs